Mythological reminiscences in the poetry of V.Ya. Bryusova - Kirichenko K. N. (Pedagogy, Psychology, Society, 2023)
The article discusses approaches to defining the concept of “reminiscence”, analyzes mythological reminiscences in the lyrics of V.Ya. Bryusov: the dominant mythological motifs and images in his poetic work have been studied, Bryusov’s poems have been compared with the lyrics of the ancient Greek poetess Sappho, the specifics of the use of mythological reminiscences have been determined. The tendencies of Bryusov's lyrics are also compared with the peculiarities of O.E.'s creativity. Mandelstam.
Keywords: миф; myth; реминисценция; Сапфо; V.Ya. Bryusov; reminiscence; Sappho; O.E. Mandelstam; Брюсов В.Я.; Мандельштам О.Э